Anti‐glycation and inhibition of starch hydrolyzing enzymes by enzymatically hydrolysed djulis (Chenopodium formosanum Koidz.) hull, leaf and seedling. (6th September 2021) - Chen, Jing‐Yu; Sridhar, Kandi; Tsai, Pi‐Jen
Summary: Glycation is the reaction of the carbonyl group of the reducing sugars to form advanced glycation end products (AGEs), which are major contributors to glycation‐related diabetes. Hence, it is necessary to find an alternative approach in management of diabetes that can reduce the formation of AGEs. Therefore, we investigated the anti‐glycation and starch hydrolysing enzymes inhibition by djulis ( Chenopodium formosanum Koidz.) hull, leaf and seedling treated with enzymatic hydrolysis (EH) and studied the possible phenolic compounds responsible for the anti‐glycation efficacy. Djulis samples treated with EH showed a high inhibitory effect on AGEs (65.04–72.77%), methylglyoxal (80.01–90.70%), α‐amylase (86.37–93.50%) and α‐glucosidase (35.50–38.16%). Bioactive compounds were significantly contributed to the anti‐glycation potential of djulis samples. Therefore, djulis hull, leaf and seedling treated with EH could be used as a natural potential source in the prevention of glycation‐associated diabetes, health risks and to increase food productivity. Abstract : Enzymatically hydrolysed djulis ( Chenopodium formosanum Koidz .) hull, leaf and seedling are potential sources in the prevention of glycation‐associated diabetes.